Kepatuhan Rumah Ibadah Dalam Penerapan Protokol Kesehatan Covid-19 Di Era New Normal - Muhammad Mudhofar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The issuance of Circular Number 15 of 2020 by the Minister of Religion concerning Guidelines for the Implementation of Religious Activities in House of worship in Realizing a Productive and Safe Society Covid in the Pandemic Period, is a response to the longing of religious communities to return to worship in their respective places of worship, including Muslims after the limitation and even prohibition by the government. This research was conducted at the Great Mosque Anas Machfudz in Lumajang Regency with the aim of analyzing the compliance of administrators and congregations mosque, as well as inhibiting and supporting factors for the implementation of the Covid-19 health protocol according to the Circular of the Ministry of Religion. This type of research is descriptive qualitative with data analysis techniques interactive model of analysis. The results showed that of administrators and congregations mosque had followed the guidelines well. Supporting factors for compliance with guidelines are active socialization by the administrators mosque, availability of personal protective equipment facilities, the formation of a covid-19 prevention team, and the existence of a health post. Inhibiting factors are the sub-optimal role of mosque youth, differences in perceptions of guidelines, the absence of strict punishment or sanctions, and imperfect regulations in technical guidelines.